Advances of Green‐Synthesized Nanoparticles for Biomedical Applications. - Mobarak, Md Hosne; Al Mahmud, Md. Zobair; Hossain, Amran; Abir, Md. Arman Hossain; Hossain, Nayem; Chowdhury, Mohammad Asaduzzaman; Banerjee, Baisakhi (BioMed Research International, 2026)
In biomedical nanotechnology, plant‐mediated production of metallic nanoparticles has become a viable and physiologically adaptable method that offers decreased toxicity, enhanced biocompatibility, and functional surface modification by phytochemical capping. In addition to altering physicochemical characteristics, including size, shape, crystallinity, and surface charge, plant extracts also function as reducing, stabilizing, and capping agents, allowing for controlled nanoparticle production. Antimicrobial efficacy, cytotoxic selectivity, antioxidant activity, and interactions with mammalian cells are among the properties that significantly influence biological performance. The mechanistic knowledge of nanoparticle production and structure–activity correlations has been made easier by developments in spectroscopic, microscopic, and surface analytical methods. When taken as a whole, plant‐derived nanoparticles show encouraging biomedical potential in antimicrobial therapy, anticancer applications, wound healing, and drug delivery assisted by nanocarriers. However, they also pose issues with standardization, reproducibility, and translational scalability. This semisystematic review summarizes recent advancements in the synthesis, characterization, and biomedical applications of plant‐derived nanoparticles, highlighting quantitative trends, mechanistic insights, and important knowledge gaps pertinent to future clinical translation. It covers literature from 2015 to 2024 and analyzes over 120 studies.